Seminar Smart Parenting di Era Digital - Aufia Aisa; Rina Dian Rahmawati; Amrini Shofiyani; Muhammad Subhan; Evi Endha Lestari; Fahmi Najah Umami; Ummi Nur Jannah (Lembaga Penelitian dan Pengabdian Masyarakat UNWAHA, 2024)
The lack of understanding of the Gambiran Village community regarding smart parenting in forming children's character in the digital era is the basis for holding a